Embracing networks of national policy research in future foresight. (2016) - Kim, Hyunuk; You, Taekho; Ahn, Sang-Jin; Jung, Woo-Sung
Policy research on social issues usually has been led by the national government. Policy research reflects national interests in the present as well as in the future. In this paper, we examine a possibility to apply network analysis of national policy research in future foresight. Network analysis is conducted based on the bibliometric data retrieved from the National Knowledge Information System (NKIS) of Korea which helps public to find national research papers with ease. We classify these issues into three categories (national security, economy, and social problem), and calculated centrality measures to detect important social issues and keywords. Keywords with high betweenness centrality show detailed social trends in Korea.